FAKTOR-FAKTOR YANG MEMPENGARUHI KESIAPAN PEREMPUAN DALAM MENGHADAPI MASA MENOPAUSE - Nessi Meilan; Nurul Huda (Jurnal Fisioterapi dan Kesehatan Indonesia, 2022)
Based on data in 2020 on mothers aged 40-50 years visits, who experienced menopausal symptoms in the Balai Kota DKI Jakarta health service unit as many as 35 people among complaints such as irregularities of the menstrual cycle, sweat a lot, insomnia, hypertension, fatigue quickly, spinal pain, bone loss, blood circulation disorders, increased weight. Women who experience the premenopausal phase experience some physical and psychological changes (Rediyanati, 2011). The impact of changes in the climatterium phase in women is that women feel many complaints, but between one women and the other is different because of biological effects and individual reactions due to low estrogen that cause different symptoms. The impact caused is that women become less confident because they experience or lack of acceptance of the physical and psychic changes experienced. This excessive anxiety and fear can affect the level of readiness so that women need knowledge and readiness both related to physical and psychological changes that will be faced (Fitriani, 2012). Women of menopause age will experience many health risks so it is appropriate that great attention to prepare women for menopause should be given. The purpose of the study was to find out the factors that affect the readiness of mothers in facing menopause. This study used an analytical quantitative type with a Cross Sectional design with a sample of 32 mothers aged 40-50 years and purposive sampling techniques. The results of the study found a meaningful relationship between education (p value 0.039), knowledge level (value p 0.015) and complaints (value p 0.039) with the readiness of mothers facing menopause. Recommendations for Midwives and the government should provide better Health Education for woman with the age leading up to Menopause so that with increasing knowledge can make the mother better prepared for her menopause period. Key words : woman, menopause, readiness